Effects of Disintegration between Agriculture and Livestock Keeping on Transhumance Pastoralism in Gorkha - Gurung, Dil Bahadur (Khwopa Journal, 2024)
Livestock keeping is an important livelihood option in rural households of Nepal. The livestock keeping is also directly associated with the local agriculture. The farmers residing at the lower valley (foothill) of rural hilly villages collect manure from their livestocks and transfer these manure to their farming land to recharge the soil and to increase the agricultural production. In hilly and high altitude areas, the need of manure to the local farmers are also fulfilled by the sheep herding practices (transhumance pastoralism). However, the livestock keeping practices have been declining in the hilly areas due to various reasons through out the years, affecting the agricultural practices and production. Side by side, livestock data of Nepal shows that the sheep count is declining gradually which means the transhumance pastoralism (sheep herding) is also declining. This led to shrink in supply of sheep manure, further mounting challeges to the local farmers and agricultural production. The general objective of the study is to explore the factors behind the disintegration of agricluture and livestock keeping practices in the hilly areas and its association with the shrinking transhumance pastoralsim. The researcher implemented an exploratory research design and conducted in-depth interviews with 12 herders, two ex-herders, one president of the community forest user group, two teachers, and two local citizen. The responses from interviews suggest that emerging market system, labor migration, and community forest programs are the main factors for disintegrating the relationship between livestock keeping and agricultural practices that led to waning of sheep herding practices at the high altitude areas